2020
DOI: 10.7150/ntno.39804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular weight and structural conformation of multivalent-based elastin-like polypeptides on tumor accumulation and tissue biodistribution

Abstract: In order to improve clinical outcomes for novel drug delivery systems, distinct optimization of size, shape, multifunctionality, and site-specificity are of utmost importance. In this study, we designed various multivalent elastin-like polypeptide (ELP)-based tumor-targeting polymers in which multiple copies of IL-4 receptor (IL-4R)-targeting ligand (AP1 peptide) were periodically incorporated into the ELP polymer backbone to enhance the affinity and avidity towards tumor cells expressing high levels of IL-4R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the concrete guest residue and peptide length of ELPs need to be optimized for drug delivery to different tumor types. Sarangthem V indicated that increased molecular weight of AP1-ELPs contributes to better tumor penetration and retention in 4T1 tumor-bearing mice ( Sarangthem et al, 2020 ). Kuna M also demonstrated that the increased molecular weight of ELPs had longer plasma half-lives and higher total renal accumulation ( Kuna et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concrete guest residue and peptide length of ELPs need to be optimized for drug delivery to different tumor types. Sarangthem V indicated that increased molecular weight of AP1-ELPs contributes to better tumor penetration and retention in 4T1 tumor-bearing mice ( Sarangthem et al, 2020 ). Kuna M also demonstrated that the increased molecular weight of ELPs had longer plasma half-lives and higher total renal accumulation ( Kuna et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the potential of micelle-forming multivalent targeting based AP1-ELP (A86) polymers, emphasizing their heightened binding activity, rapid cellular entry, and efficient processing within the interleukin-4 receptor (IL-4R)-dependent endocytic pathway across diverse cancer cell lines [ 44 ]. Exclusively, A86 exhibited superior tumor penetration and substantial retention within tumor tissues while also mitigating non-specific accumulation in critical organs in a murine model with 4T1 allografted tumors.…”
Section: Introductionmentioning
confidence: 99%